1980
DOI: 10.1094/phyto-70-214
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Tobacco Yellow Dwarf and Bean Summer Death Viruses

Abstract: Tobacco yellow dwarf and bean summer death diseases apparently are absorbance typical of a nucleoprotein, contain a single centrifugal confined to Australia, and the. causal pathogens are transmitted •by the component with a sedimentation coefficient of 76S, and yield a single leafhopper Orosius argentatus. The diseases were shown to be caused by structural protein species of molecular weight 27,500. The yield of TYDV viruses. Purified preparations obtained from Datura stramonium plants, was about 100-250 Ag/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Firstly, the infectious unit of the genome comprises as showing that a bipartite genome is not a common feature of only a single DNA component analogous to DNA 1. On the basis of the similarities of genome organisation between BCTV and other geminiviruses and the fact that the majority of geminiviruses, including the serologically related tobacco yellow dwarf virus (Thomas and Bowyer, 1980), have a single predominant coat protein, it is suggested that the presence of two coat protein species reflects a mixed population within the native virus isolate rather than translational strategy or post-translational modification. Secondly, the putative coat genome length of only 2993 nucleotides, this places BCTV among protein of BGTV is more closely related to those of leafhopperthe smallest viral pathogens of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the infectious unit of the genome comprises as showing that a bipartite genome is not a common feature of only a single DNA component analogous to DNA 1. On the basis of the similarities of genome organisation between BCTV and other geminiviruses and the fact that the majority of geminiviruses, including the serologically related tobacco yellow dwarf virus (Thomas and Bowyer, 1980), have a single predominant coat protein, it is suggested that the presence of two coat protein species reflects a mixed population within the native virus isolate rather than translational strategy or post-translational modification. Secondly, the putative coat genome length of only 2993 nucleotides, this places BCTV among protein of BGTV is more closely related to those of leafhopperthe smallest viral pathogens of eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION Serology or amino acid composition of capsid proteins are commonly used to suggest phylogenies of plant viruses (Shukla & Ward, 1988;Fauquet et al, 1986). Serological studies of geminiviruses have shown that whitefly-transmitted geminiviruses are related sufficiently to cross-react with polyclonal and monoclonal antisera; however, there is a general lack of serological cross-reactivity among leafhopper-transmitted geminiviruses (Roberts et al, 1984), with the exceptions of MSV and DSV (Dollet et al, 1986) and BCTV and tobacco yellow dwarf virus (Thomas & Bowyer, 1980). No antigenic cross-reactivity has been substantiated between whitefly-and leafhopper-transmitted geminiviruses (Thomas et al, 1986).…”
Section: Comparison Of Coat Proteinsmentioning
confidence: 99%
“…Of these viruses, ACMV, BGMV, SLCV and TomGMV are transmitted by the whitefly Bemisia tabaci, whereas the others have leafhopper vectors. The only serological relationship reported among leafhoppertransmitted geminiviruses is that between BCTV and tobacco yellow dwarf virus (TYDV; Thomas & Bowyer, 1980).…”
Section: Introductionmentioning
confidence: 99%